17p12 Influences Hematoma Volume and Outcome in Spontaneous Intracerebral Hemorrhage. Issue 7 (July 2018) - Marini, Sandro; Devan, William J.; Radmanesh, Farid; Miyares, Laura; Poterba, Timothy; Hansen, Björn M.; Norrving, Bo; Jimenez-Conde, Jordi; Giralt-Steinhauer, Eva; Elosua, Roberto; Cuadrado-Godia, Elisa; Soriano, Carolina; et al.
Abstract : Background and Purpose—: Hematoma volume is an important determinant of clinical outcome in spontaneous intracerebral hemorrhage (ICH). We performed a genome-wide association study (GWAS) of hematoma volume with the aim of identifying novel biological pathways involved in the pathophysiology of primary brain injury in ICH. Methods—: We conducted a 2-stage (discovery and replication) case-only genome-wide association study in patients with ICH of European ancestry. We utilized the admission head computed tomography to calculate hematoma volume via semiautomated computer-assisted technique. After quality control and imputation, 7 million genetic variants were available for association testing with ICH volume, which was performed separately in lobar and nonlobar ICH cases using linear regression. Signals with P <5×10 − 8 were pursued in replication and tested for association with admission Glasgow coma scale and 3-month post-ICH dichotomized (0–2 versus 3–6) modified Rankin Scale using ordinal and logistic regression, respectively. Results—: The discovery phase included 394 ICH cases (228 lobar and 166 nonlobar) and identified 2 susceptibility loci: a genomic region on 22q13 encompassing PARVB (top single-nucleotide polymorphism rs9614326: β, 1.84; SE, 0.32; P =4.4×10 −8 ) for lobar ICH volume and an intergenic region overlying numerous copy number variants on 17p12 (top single-nucleotide polymorphism rs11655160: β, 0.95; SE, 0.17; P =4.3×10 −8 ) for nonlobar ICH volume. The replication included 240 ICH cases (71 lobar and 169 nonlobar) and corroborated the association for 17p12 ( P =0.04; meta-analysis P =2.5×10 −9 ; heterogeneity, P =0.16) but not for 22q13 ( P =0.49). In multivariable analysis, rs11655160 was also associated with lower admission Glasgow coma scale (odds ratio, 0.17; P =0.004) and increased risk of poor 3-month modified Rankin Scale (odds ratio, 1.94; P =0.045). Conclusions—: We identified 17p12 as a novel susceptibility risk locus for hematoma volume, clinical severity, and functional outcome in nonlobar ICH. Replication in other ethnicities and follow-up translational studies are needed to elucidate the mechanism mediating the observed association. Abstract : Supplemental Digital Content is available in the text.